2004
DOI: 10.1211/0022357044733
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of Terminalia catappa L. leaves and its two triterpenoids

Abstract: The aim of this study was to evaluate the effect of the chloroform extract of Terminalia catappa L. leaves (TCCE) on carbon tetrachloride (CCl(4))-induced acute liver damage and D-galactosamine (D-GalN)-induced hepatocyte injury. Moreover, the effects of ursolic acid and asiatic acid, two isolated components of TCCE, on mitochondria and free radicals were investigated to determine the mechanism underlying the action of TCCE on hepatotoxicity. In the acute hepatic damage test, remarkable rises in the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 25 publications
3
43
0
1
Order By: Relevance
“…Pretreatment with AA reduced ROS levels in Glu-injured cells (Figure 3). These results are consistent with those of our previous study, which showed that AA has hydroxyl radical-scavenging activity in cell-free systems [40] . The disruption of the MMP may lead to cytochrome c release and activation of caspases that may lead to cell death.…”
Section: Discussionsupporting
confidence: 94%
“…Pretreatment with AA reduced ROS levels in Glu-injured cells (Figure 3). These results are consistent with those of our previous study, which showed that AA has hydroxyl radical-scavenging activity in cell-free systems [40] . The disruption of the MMP may lead to cytochrome c release and activation of caspases that may lead to cell death.…”
Section: Discussionsupporting
confidence: 94%
“…The AA neuroprotective effect was also confirmed with the H 2 O 2 -induced damage. It is consistent with our previous study that AA has hydroxyl radicals scavenging activity [41] . The concentration of AA is critical for its neuroprotection.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the activities of SOD and GPx were found to be decreased in the liver mitochondria of D-GalN-induced hepatotoxicity rats, which is probably due to an accumulation of ROS and severe oxidative stress by D-GalN. GSH is a major defence mechanism against oxidative stress within mitochondria [44]. The depletion in the levels of mitochondrial GSH seems to be a major mechanism in inducing an imbalance of mitochondrial function [45].…”
Section: Discussionmentioning
confidence: 46%
“…GSH depletion and/or increased free radical accumulation may lead to the decrease in the levels of ascorbic acid and a-tocopherol in the liver toxicity rats, which was also observed our study. This condition may aggravate the overproduction of mitochondrial ROS [44]. Treatment with carvacrol reversed these changes towards normality.…”
Section: Discussionmentioning
confidence: 97%